(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article discusses an important issue of Ukrainian and global management - diversity in the workplace. It has been found that diversity in the workplace is becoming increasingly important in today’s business environment, as society becomes more globalized and open to different cultural, gender, and age groups. The article examines the definitions of the concepts of "diversity", "diversity management", "inclusiveness", "organizational culture", and explores the nature and types of diversity. The main aspects of diversity, such as ethnic, gender, age and cultural differences, are revealed, and statistics and trends in diversity aspects are provided. The problems that arise when implementing diversity in the workplace are analyzed, including ethical aspects and openness to diversity, as well as internal and external factors that create possible obstacles. The positive effects of diversity in the workplace, such as increased creativity, innovation and competitive advantage, are discussed. However, it also highlights possible conflicts and communication problems, as well as the challenges associated with adaptation and staff training. Diversity management practices on the example of specific Ukrainian companies are analyzed and the importance of creating an open and inclusive environment is highlighted. In conclusion, diversity management in the workplace is important for Ukrainian organizations and its impact on management. The article identifies and characterizes key aspects of diversity management: promoting productivity and innovation, reducing the risk of employee loss and increasing staff engagement, improving the company’s reputation and opening up new business opportunities, including markets with different cultural and gender characteristics. It is substantiated that diversity management in the workplace is of strategic importance for Ukrainian organizations, thereby creating conditions for sustainable development, competitiveness and improvement of the corporate climate, and contributes to the successful functioning and achievement of business goals.